Psychological characteristics of women with problems of the facial skin: relationship with age, diagnosis, effectiveness of treatment - E. S. Bagnenko (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Summary. In order to study the correlation of clinical-biological and socio-psychological characteristics of women with cosmetological problems of the skin of the face using a complex of methods of clinical, clinical-psychological and psychometric diagnostics, 110 patients of the cosmetology clinic were studied and were divided into four diagnostic groups («Gravitational ptosis»,»Mimic wrinkles»,»Acne»,»Skin dehydration»). The average age of the sample was 35.64 ± 1.11 years. The specific objectives of the study were to study the relationship between age, clinical and psychological characteristics of patients; the effectiveness of cosmetological treatment and the psychological characteristics of the patients; the degree of influence of the cosmetological problem on the vital activity and psychological characteristics of the patients; attitude towards oneself and other psychological characteristics of women with facial skin defects.Based on the analysis of special literature and the results of our own research, it is shown that it is necessary to study the relationship of psychological and clinical-biological factors for the individualization of the process of cosmetological correction of the facial skin.A statistically significant relationship was established between age and clinical diagnosis, between age and psychological characteristics of patients. It has been proven that subjective satisfaction with the results of treatment positively correlates with extraversion and self-confidence, as well as with an objective assessment of the effectiveness of treatment, which in turn is interrelated with patient satisfaction with their social and professional status, as well as with the internal orientation of the personality - factors that contribute to compliance. and partnership in the treatment process.It was revealed: the higher the severity of the facial skin defect, the more self-doubt, inability to cooperate and cooperate in the personality structure, and the lower the expert assessment of the effectiveness of treatment.